Dielectric and method of manufacturing the same
Patent Information
- Application Number
- JP2024001134
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-10-07
- Filing Date
- 2024-01-09
- Publication Date
- 2026-10-14
AI Technical Summary
Existing high-frequency printed wiring boards face challenges with frequency-dependent relative permittivity, anisotropy of dielectric constant, and high dielectric loss tangent, leading to complex wiring designs and increased transmission loss.
A dielectric material composed of a fluororesin and spherical fillers, such as silica, with specific properties like a relative permittivity slope of 0.00001 to 0.0005 from 220 to 330 GHz, 90° anisotropy of 0.02 or less, and dielectric loss tangents of 0.00153 or less at 220 GHz and 0.00165 or less at 330 GHz, is developed.
The material reduces frequency dependence of dielectric constant, minimizes anisotropy, and lowers dielectric loss tangent, allowing for consistent wiring designs across a wide frequency range and reduced transmission loss.
Abstract
Description
[Technical field]
[0001] The present disclosure relates to dielectrics and methods for making same. [Background technology]
[0002] There is a demand for high-frequency printed wiring boards with small transmission loss. It is known that fluororesin films are used in such high-frequency printed wiring boards (Patent Document 1, etc.). In addition, Patent Documents 2 and 3 describe the use of fluororesin containing filler as a wiring board material.
[0003] Furthermore, Patent Document 4 discloses that a fluororesin composition in which spherical silica particles are blended with a fluororesin is used for a circuit board. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication 2015-8260 [Patent Document 2] Japanese Patent Application Publication No. 63-259907 [Patent Document 3] Special table 2022-510017 [Patent Document 4] International Publication 2020 / 145133 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present disclosure is to provide a dielectric material that reduces the frequency dependency of the relative dielectric constant in the terahertz high frequency band (110 to 330 GHz) and a method for producing the same. A further object of the present invention is to provide a dielectric material having a small anisotropy of the relative dielectric constant and a method for producing the same. A further object of the present invention is to provide a dielectric material having a small dielectric tangent in a high frequency band and a method for producing the same. [Means for solving the problem]
[0006] The present disclosure relates to a dielectric material characterized in that the slope of the relative dielectric constant (Dk) with respect to frequencies from 220 GHz to 330 GHz measured in the J band using a Fabry-Perot resonator is equal to or greater than 0.00001 and equal to or less than 0.0005. The present disclosure also relates to a dielectric material characterized in that the 90° anisotropy in the planar direction of the relative dielectric constant (Dk) at 170 GHz measured in the J band of a Fabry-Perot resonator is 0.02 or less.
[0007] The present disclosure also relates to a dielectric material characterized in that the dielectric loss tangent (Df) at 220 GHz measured using a Fabry-Perot resonator in J-band is 0.00153 or less. The present disclosure also relates to a dielectric material characterized in that the dielectric loss tangent (Df) at 330 GHz measured using a Fabry-Perot resonator in J-band is 0.00165 or less.
[0008] The dielectric material preferably contains a resin and a spherical filler. The filler is preferably at least one selected from the group consisting of silica, titanium oxide, alumina, and forsterite. The filler is preferably comprised solely of spherical silica. The filler preferably has an average particle size of 0.1 to 10 μm.
[0009] The resin is preferably a fluororesin. The above-mentioned fluororesin is preferably composed in whole or in part of at least one polymer selected from the group consisting of polytetrafluoroethylene resin, tetrafluoroethylene-perfluoroalkylvinyl ether copolymer, and tetrafluoroethylene-hexafluoropropylene copolymer. The dielectric material is preferably obtained by using fluororesin particles having a primary particle size of 0.05 to 10 μm as a raw material.
[0010] The fluororesin particles preferably have a volume-based cumulative 50% diameter of 0.05 to 40 μm. The dielectric material is It is preferable that the material be used for a printed circuit board for the terahertz band, a dielectric material for the terahertz band, or a laminated circuit board for the terahertz band. The dielectric material preferably has a sheet shape.
[0011] The present disclosure also provides a method for producing the above-mentioned dielectric material, which comprises a step of mixing fluororesin particles and a filler to form a film. In the method for producing the dielectric material, it is preferable to form a film by mixing only the fluororesin particles and the filler, without adding any other components.
[0012] The present disclosure is also a copper clad laminate having as essential layers a copper foil and the dielectric material described above. The present disclosure also relates to a circuit board comprising the above-mentioned copper clad laminate. Effect of the Invention
[0013] The dielectric material according to the present disclosure can reduce the frequency dependence of the dielectric constant in the terahertz high frequency band. Furthermore, the anisotropy of the relative dielectric constant can be reduced. Furthermore, the dielectric loss tangent in the high frequency band can be made small. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present disclosure will be described in detail below. In recent years, as electronic products have become increasingly high-frequency, there has been a demand for wiring boards to have performance that can withstand high frequencies. First, it is not desirable for the dielectric constant to vary with frequency in the high frequency band. When such a dielectric is made into a copper-clad laminate, the wiring width of the copper wiring must be changed for each frequency, which makes the wiring complicated. Furthermore, if the wiring width cannot be changed, it can only be used at specific frequencies. Therefore, in order to prevent such a state from occurring, it is necessary to obtain a dielectric material whose relative dielectric constant has a small frequency dependency. Secondly, it is desirable to obtain a dielectric material having a small anisotropy of the relative dielectric constant in the high frequency band. The anisotropy of the relative dielectric constant is undesirable in that when a copper clad laminate is formed, the copper wiring is designed to be other than linear, and the wiring width must be changed depending on the direction. Furthermore, it is preferable that the dielectric loss tangent (Df) for each frequency of 220 GHz and 330 GHz is low. Since the fluororesin dielectric is used for the purpose of obtaining a low-loss material with low transmission loss of high-frequency signals by using a dielectric material with a low dielectric loss tangent, it is preferable that the dielectric loss tangent value is small. The objective of the present disclosure is to obtain a dielectric material having these properties.
[0015] (Frequency dependence of dielectric constant) The first dielectric material of the present disclosure has a gradient of the relative dielectric constant (Dk) with respect to frequencies from 220 GHz to 330 GHz, measured using a Fabry-Perot resonator in the J band, of 0.00001 or more and 0.0005 or less. In other words, this means that the frequency dependency of the relative dielectric constant in the high frequency band is small.
[0016] In this disclosure, the dielectric constant (Dk) and dielectric loss tangent (Df) were measured at each frequency using a network analyzer (N5290a, Keysight Technologies) and a Fabry-Perot resonator (EM Lab) at room temperature of 25°C and humidity of 50%.
[0017] Furthermore, the slope of the relative dielectric constant was calculated by plotting the values of the relative dielectric constant from 220 GHz to 330 GHz.
[0018] When the above slope is 0.00001 or more and 0.0005 or less, it is not necessary to change the wiring width of the copper wiring for each frequency when it is made into a copper clad laminate. Also, it can be used at a wide range of frequencies. The above upper limit is more preferably 0.0004, and even more preferably 0.0002.
[0019] (Anisotropy of dielectric constant) The second dielectric material of the present disclosure has a 90° anisotropy in the in-plane direction of the relative dielectric constant (Dk) at 170 GHz of 0.02 or less. In other words, this means that the anisotropy of the relative dielectric constant in the high frequency band is small.
[0020] Furthermore, the 90° anisotropy of the dielectric constant in the planar direction was calculated by measuring the dielectric constant (Dk) at 170 GHz in the planar directions of 0° and 90° using a network analyzer (N5290A, Keysight Technologies) and a Fabry-Perot resonator (EM Lab) at room temperature of 25°C and humidity of 50%, and calculating the difference.
[0021] The anisotropy of 0.02 or less is preferable because when designing the copper wiring in a direction other than a straight line, there is no need to change the wiring width depending on the direction. The upper limit is more preferably 0.018, and even more preferably 0.016.
[0022] (Dielectric loss tangent (Df) at 220GHz) The third dielectric of the present disclosure has a dielectric loss tangent of 0.00153 or less at 220 GHz. That is, by having such a dielectric loss tangent, it has an effect of low loss, that is, low transmission loss of high frequency signals. The upper limit is more preferably 0.00152, and even more preferably 0.00151. The lower limit is not particularly limited, but is more preferably 0. In this specification, the dielectric loss tangent was measured at room temperature of 25°C and humidity of 50% using a network analyzer (N5290A, Keysight Technologies) and a Fabry-Perot resonator (EM Lab).
[0023] (Dielectric loss tangent (Df) at 330GHz) The fourth dielectric of the present disclosure has a dielectric loss tangent of 0.00165 or less. That is, by having such a dielectric loss tangent, it has an effect of low loss, that is, low transmission loss of high frequency signals. The upper limit is more preferably 0.00164, and even more preferably 0.00163. The lower limit is not particularly limited, but is more preferably 0.
[0024] The dielectric material of the present disclosure may have any one of the first to fourth properties described above, may have two or more of the properties in combination, or may have all of the properties in combination.
[0025] (Dielectric) The dielectric of the present disclosure is not particularly limited as long as it satisfies any of the above-mentioned parameters, but is preferably a composition containing a spherical filler and a fluororesin. In such a composition, the composition can be adjusted as necessary to obtain a dielectric that satisfies the above-mentioned parameters. The spherical filler and fluororesin that can be used in such a dielectric are described in detail below.
[0026] (Fluorine resin) The fluororesin sheet of the present disclosure contains a fluororesin. Since the fluororesin has low dielectric properties, it can be suitably used for the purpose of the present disclosure.
[0027] The fluororesin that can be used in the present disclosure is not particularly limited, and examples thereof include polytetrafluoroethylene [PTFE], tetrafluoroethylene [TFE] / hexafluoropropylene [HFP] copolymer [FEP], TFE / alkyl vinyl ether copolymer [PFA], TFE / HFP / alkyl vinyl ether copolymer [EPA], TFE / chlorotrifluoroethylene [CTFE] copolymer, TFE / ethylene copolymer [ETFE], polyvinylidene fluoride [PVdF], tetrafluoroethylene having a molecular weight of 300,000 or less [LMW-PTFE], etc. One type may be used, or two or more types may be mixed. From the viewpoint of low dielectric properties, the above-mentioned fluororesin is preferably polytetrafluoroethylene resin (PTFE), tetrafluoroethylene [TFE] / hexafluoropropylene [HFP] copolymer [FEP], or TFE / alkyl vinyl ether copolymer [PFA], and is particularly preferably polytetrafluoroethylene resin (PTFE). PTFE having fibrillation properties is preferable. PTFE having fibrillation properties means PTFE that can be paste-extruded from unsintered polymer powder.
[0028] (Polytetrafluoroethylene) PTFE may be modified polytetrafluoroethylene (hereinafter referred to as modified PTFE), homopolytetrafluoroethylene (hereinafter referred to as homoPTFE), or a mixture of modified PTFE and homoPTFE. From the viewpoint of maintaining good moldability of polytetrafluoroethylene, the content of modified PTFE in the polymeric PTFE is preferably 10% by weight or more and 98% by weight or less, and more preferably 50% by weight or more and 95% by weight or less. The homo-PTFE is not particularly limited, and homo-PTFE disclosed in JP-A-53-60979, JP-A-57-135, JP-A-61-16907, JP-A-62-104816, JP-A-62-190206, JP-A-63-137906, JP-A-2000-143727, JP-A-2002-201217, WO 2007 / 046345 pamphlet, WO 2007 / 119829 pamphlet, WO 2009 / 001894 pamphlet, WO 2010 / 113950 pamphlet, WO 2013 / 027850 pamphlet, etc. can be suitably used. Among these, homo-PTFE having high stretchability and disclosed in JP-A-57-135, JP-A-63-137906, JP-A-2000-143727, JP-A-2002-201217, WO 2007 / 046345, WO 2007 / 119829, WO 2010 / 113950 and the like is preferred.
[0029] The modified PTFE is composed of TFE and a monomer other than TFE (hereinafter referred to as a modified monomer). The modified PTFE may be, but is not limited to, one that is uniformly modified by the modified monomer, one that is modified at the beginning of the polymerization reaction, one that is modified at the end of the polymerization reaction, etc. The modified PTFE is preferably a TFE copolymer obtained by subjecting a small amount of a monomer other than TFE to polymerization together with TFE within a range that does not significantly impair the properties of the TFE homopolymer. The modified PTFE may be, for example, those disclosed in JP-A-60-42446, JP-A-61-16907, JP-A-62-104816, JP-A-62-190206, JP-A-64-1711, JP-A-2-261810, JP-A-11-240917, JP-A-11-240918, WO 2003 / 033555 pamphlet, WO 2005 / 061567 pamphlet, WO 2007 / 005361 pamphlet, WO 2011 / 055824 pamphlet, WO 2013 / 027850 pamphlet, etc., which can be suitably used. Among these, modified PTFEs having high stretchability and disclosed in JP-A-61-16907, JP-A-62-104816, JP-A-64-1711, JP-A-11-240917, WO 2003 / 033555, WO 2005 / 061567, WO 2007 / 005361, WO 2011 / 055824 and the like are preferred.
[0030] The modified PTFE contains TFE units based on TFE and modified monomer units based on modified monomers. The modified monomer units are a part of the molecular structure of the modified PTFE and are derived from the modified monomer. The modified PTFE contains the modified monomer units in an amount of preferably 0.001 to 0.500% by weight, more preferably 0.01 to 0.30% by weight, of the total monomer units. The total monomer units are the parts derived from all monomers in the molecular structure of the modified PTFE.
[0031] The modifying monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene (HFP), chlorofluoroolefins such as chlorotrifluoroethylene (CTFE), hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride (VDF), perfluorovinyl ethers, perfluoroalkylethylenes (PFAE), ethylene, etc. The modifying monomer used may be one type or multiple types.
[0032] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorounsaturated compounds represented by the following general formula (1). CF2 = CF-ORf (1)
[0033] In the formula, Rf represents a perfluoro organic group.
[0034] In this specification, a perfluoro organic group is an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The perfluoro organic group may have an ether oxygen.
[0035] An example of the perfluorovinyl ether is perfluoro(alkyl vinyl ether) (PAVE) in which Rf in the above general formula (1) is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5. Examples of the perfluoroalkyl group in PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group. Preferred examples of PAVE include perfluoropropyl vinyl ether (PPVE) and perfluoromethyl vinyl ether (PMVE).
[0036] The perfluoroalkylethylene (PFAE) is not particularly limited, and examples thereof include perfluorobutylethylene (PFBE), perfluorohexylethylene (PFHE), and the like.
[0037] The modifying monomer in the modified PTFE is preferably at least one selected from the group consisting of HFP, CTFE, VDF, PAVE, PFAE and ethylene.
[0038] The fluororesin is preferably non-melt moldable, meaning that the resin does not have sufficient fluidity even when heated to the melting point or higher and cannot be molded by a melt molding method generally used for resins.
[0039] In the present disclosure, it is preferable to use such a fluororesin that cannot be melt-molded, and to form the fluororesin sheet by a molding method that fibrillates the fluororesin. The molding method will be described later.
[0040] The PTFE preferably has an SSG of 2.0 to 2.3. When such a PTFE is used, a PTFE membrane having high strength (cohesion and puncture strength per unit thickness) is easily obtained. Since a PTFE having a large molecular weight has a long molecular chain, it is difficult to form a structure in which the molecular chains are regularly arranged. In this case, the length of the amorphous part increases, and the degree of entanglement between the molecules increases. When the degree of entanglement between the molecules is high, the PTFE membrane is unlikely to deform under an applied load and is considered to exhibit excellent mechanical strength. In addition, when a PTFE having a large molecular weight is used, a PTFE membrane having a small average pore size is easily obtained.
[0041] The lower limit of the SSG is more preferably 2.05, and even more preferably 2.1. The upper limit of the SSG is more preferably 2.25, and even more preferably 2.2.
[0042] Standard specific gravity (SSG) was measured by preparing a sample in accordance with ASTM D-4895-89 and measuring the specific gravity of the resulting sample by the water displacement method.
[0043] In this embodiment, the molecular weight (number average molecular weight) of the PTFE constituting the PTFE powder is, for example, in the range of 2 million to 12 million. The lower limit of the molecular weight of the PTFE may be 3 million or 4 million. The upper limit of the molecular weight of the PTFE may be 10 million.
[0044] The number average molecular weight of PTFE can be measured by a method based on standard specific gravity and a method based on dynamic viscoelasticity when melted. The method based on standard specific gravity can be performed by a water displacement method based on ASTM D-792 using a sample molded based on ASTM D-4895 98. The method based on dynamic viscoelasticity is described, for example, by S. Wu in Polymer Engineering & Science, 1988, Vol. 28, 538 and the same document, 1989, Vol. 29, 273.
[0045] The PTFE preferably has a maximum endothermic peak temperature (crystalline melting point) of 340±7°C.
[0046] The PTFE may be a low-melting-point PTFE having a maximum peak temperature of 338°C or lower on the endothermic curve on a crystalline melting curve measured by a differential scanning calorimeter, or a high-melting-point PTFE having a maximum peak temperature of 342°C or higher on the endothermic curve on a crystalline melting curve measured by a differential scanning calorimeter.
[0047] Low-melting-point PTFE is a powder produced by emulsion polymerization, and has the above-mentioned maximum endothermic peak temperature (crystalline melting point), a dielectric constant (ε) of 2.08 to 2.2, and a dielectric tangent (tan δ) of 1.9×10 -4 ~4.0×10 -4 Examples of commercially available products include Polyflon fine powders F201, F203, F205, F301, and F302 manufactured by Daikin Industries, Ltd., CD090 and CD076 manufactured by Asahi Glass Co., Ltd., and TF6C, TF62, and TF40 manufactured by DuPont.
[0048] The high melting point PTFE powder is also a powder produced by emulsion polymerization, and has the above-mentioned maximum endothermic peak temperature (crystalline melting point), a dielectric constant (ε) of 2.0 to 2.1, and a dielectric tangent (tan δ) of 1.6×10 -4 ~2.2×10 -4 As commercially available products, for example, Polyflon fine powder F104 and F106 manufactured by Daikin Industries, Ltd., CD1, CD141, and CD123 manufactured by Asahi Glass Co., Ltd., and TF6 and TF65 manufactured by DuPont can be mentioned.
[0049] The powder in which both PTFE polymer particles are secondary aggregated usually has an average particle size of 250 to 2000 μm. In particular, granulated powder obtained by granulation using a solvent is preferred from the viewpoint of improving the flowability when filling a mold in preforming.
[0050] Powdered PTFE that satisfies the above-mentioned parameters can be obtained by a conventional manufacturing method, for example, by following the manufacturing methods described in International Publication No. 2015-080291 and International Publication No. 2012-086710.
[0051] (Melt-moldable fluororesin) As described above, the dielectric of the present disclosure is most preferably a polytetrafluoroethylene resin. On the other hand, a melt-moldable fluororesin can also be used to obtain a molded body having the above-mentioned parameters. From this perspective, the melt-moldable fluororesin will also be described in detail below.
[0052] The fluororesin is more preferably a melt-moldable fluororesin, and examples of such fluororesin include tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), copolymers having chlorotrifluoroethylene (CTFE) units (CTFE copolymers), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-ethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), chlorotrifluoroethylene-ethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF), and polyvinyl fluoride (PVF), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer (THV), tetrafluoroethylene-vinylidene fluoride copolymer, and the like. Among these melt-moldable fluororesins, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) and tetrafluoroethylene-hexafluoropropylene copolymer (FEP) are preferred.
[0053] The resin constituting the fluororesin film preferably has a glass transition temperature of 40° C. or higher. A glass transition temperature of 40° C. or higher is preferable in that deformation at the environmental temperature is unlikely to occur, for example, when a roll film is stored at room temperature, and a glass transition temperature of 60° C. or higher is more preferable, and a glass transition temperature of 80° C. or higher is even more preferable. The upper limit is not particularly limited, but from the viewpoint of adhesion, a glass transition temperature of 200° C. or lower is preferable, a glass transition temperature of 160° C. or lower is more preferable, and a glass transition temperature of 120° C. or lower is even more preferable.
[0054] The melting point of the PFA is preferably 180 to 340° C., more preferably 230 to 330° C., and further preferably 280 to 320° C. The melting point is the temperature corresponding to the maximum value on the heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].
[0055] The PFA is not particularly limited, but is preferably a copolymer in which the molar ratio of TFE units to PAVE units (TFE units / PAVE units) is 70 / 30 or more and less than 99.5 / 0.5. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and an even more preferred molar ratio is 80 / 20 or more and 98.5 / 1.5 or less. If the TFE units are too few, the mechanical properties tend to decrease, and if the TFE units are too many, the melting point tends to become too high and moldability tends to decrease. The PFA may be a copolymer consisting of only TFE and PAVE, or it is also preferable that the monomer units derived from monomers copolymerizable with TFE and PAVE are 0.1 to 10 mol %, and the TFE units and PAVE units are 90 to 99.9 mol % in total. Examples of monomers copolymerizable with TFE and PAVE include HFP, CZ, and the like. 3 Z 4 =CZ 5 (CF2)nZ 6 (In the formula, Z 3 , Z 4 and Z 5 are the same or different and represent a hydrogen atom or a fluorine atom, Z6 represents a hydrogen atom, a fluorine atom or a chlorine atom, and n represents an integer of 2 to 10. 7 (In the formula, Rf 7 represents a perfluoroalkyl group having 1 to 5 carbon atoms.) and alkyl perfluorovinyl ether derivatives represented by the formula (I) and (II). Other copolymerizable monomers include, for example, cyclic hydrocarbon monomers having an acid anhydride group, and examples of the acid anhydride monomers include itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, and maleic anhydride. The acid anhydride monomers may be used alone or in combination of two or more.
[0056] The PFA preferably has a melt flow rate (MFR) of 0.1 to 100 g / 10 min, more preferably 0.5 to 90 g / 10 min, and even more preferably 1.0 to 85 g / 10 min. In this specification, the MFR is a value measured according to ASTM D3307 under conditions of a temperature of 372° C. and a load of 5.0 kg.
[0057] The FEP is not particularly limited, but is preferably a copolymer in which the molar ratio of TFE units to HFP units (TFE units / HFP units) is 70 / 30 or more and less than 99 / 1. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and an even more preferred molar ratio is 80 / 20 or more and 97 / 3 or less. If the TFE units are too few, the mechanical properties tend to decrease, and if the TFE units are too many, the melting point tends to become too high and the moldability tends to decrease. It is also preferred that the FEP is a copolymer in which the monomer units derived from a monomer copolymerizable with TFE and HFP are 0.1 to 10 mol %, and the total of the TFE units and HFP units is 90 to 99.9 mol %. Examples of the monomers copolymerizable with TFE and HFP include alkyl perfluorovinyl ether derivatives. Other copolymerizable monomers include, for example, cyclic hydrocarbon monomers having an acid anhydride group, and examples of the acid anhydride monomers include itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, maleic anhydride, etc. The acid anhydride monomers may be used alone or in combination of two or more.
[0058] The melting point of the FEP is preferably 150 to 320° C., more preferably 200 to 300° C., and further preferably 240 to 280° C. The melting point is the temperature corresponding to the maximum value on the heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC]. The FEP has an MFR of preferably 0.01 to 100 g / 10 min, more preferably 0.1 to 80 g / 10 min, further preferably 1 to 60 g / 10 min, and particularly preferably 1 to 50 g / 10 min.
[0059] The fewer the functional groups, the less the number of unstable terminal groups. Such fluororesins are prepared by adjusting the conditions during production (polymerization reaction), or by subjecting the fluororesin after polymerization to fluorine gas treatment, heat treatment, supercritical gas extraction treatment, or the like to reduce the number of unstable terminal groups. Fluorine gas treatment is preferred because it has excellent treatment efficiency and because a part or all of the unstable terminal groups are converted to -CF3 to become stable terminal groups. The use of fluororesins with a reduced number of unstable terminal groups is preferred because it reduces the electrostatic dissipation factor and reduces the loss of electrical signals.
[0060] The number of unstable terminal groups is not particularly limited, but is preferably 10 or more, more preferably 10 or more, most ... 6 The dielectric loss tangent is preferably 450 or less, more preferably 250 or less, further preferably 100 or less, and most preferably 50 or less. Considering the above effects, it is preferably less than 10, and more preferably 5 or less.
[0061] Specific examples of unstable terminal groups include functional groups such as -COF, -COOH free (free COOH), -COOH bonded (associated -COOH), hydroxyl groups (such as -CHOH), -CONH, -COOR (R=CH, etc.), -CFH, and -OCOO-R (normal propyl carbonate, etc.).
[0062] Specifically, the number of unstable terminal groups is measured by the following method. First, the fluororesin is melted and compression molded to produce a film having a thickness of 0.25 to 0.3 mm. This film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the fluororesin, and a difference spectrum is obtained from a base spectrum in which the fluororesin is completely fluorinated and no functional groups are present. From the absorption peaks of specific functional groups that appear in this difference spectrum, the number of carbon atoms in the fluororesin is calculated according to the following formula (A): 6 The number of unstable terminal groups per unit is calculated. N=I×K / t (A) I: Absorbance K: Correction coefficient t: film thickness (mm)
[0063] For reference, the absorption frequency, molar absorption coefficient, and correction coefficient for the unstable terminal group in this specification are shown in Table 1. The molar absorption coefficient was determined from the FT-IR measurement data of a low molecular weight model compound.
[0064] [Table 1]
[0065] The fluorination treatment can be carried out by contacting a non-fluorination-treated fluororesin with a fluorine-containing compound.
[0066] The fluorine-containing compound is not particularly limited, but may be a fluorine radical source that generates fluorine radicals under fluorination treatment conditions, such as F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, halogen fluorides (e.g., IF5, ClF3), etc.
[0067] The fluorine radical source such as F2 gas may be of 100% concentration, but from the viewpoint of safety, it is preferable to mix it with an inert gas and dilute it to 5 to 50% by mass, more preferably to dilute it to 15 to 30% by mass. Examples of the inert gas include nitrogen gas, helium gas, argon gas, etc., and nitrogen gas is preferable from the viewpoint of economy.
[0068] The conditions for the fluorination treatment are not particularly limited, and the fluorine-containing compound may be contacted with the molten fluororesin, but the treatment is usually carried out at a temperature below the melting point of the fluororesin, preferably 20 to 220°C, more preferably 100 to 200°C. The fluorination treatment is generally carried out for 1 to 30 hours, preferably 5 to 25 hours. The fluorination treatment is preferably carried out by contacting the unfluorinated fluororesin with fluorine gas (F2 gas).
[0069] In this specification, the content of each monomer unit constituting the fluororesin can be calculated by an appropriate combination of NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.
[0070] (Spherical filler) The dielectric material of the present disclosure preferably contains a filler, which is particularly preferable in that the linear expansion coefficient can be reduced by blending a filler. The filler that can be used in the present disclosure is not particularly limited, and examples thereof include organic fillers that are one or more selected from aramid fibers, polyphenyl esters, polyphenylene sulfide, polyimides, polyether ether ketones, polyphenylenes, polyamides, and wholly aromatic polyester resins, and inorganic fillers that are one or more selected from ceramics, talc, mica, alumina, zinc oxide, tin oxide, titanium oxide, silicon oxide, calcium carbonate, calcium oxide, magnesium oxide, potassium titanate, glass fibers, glass chips, glass beads, silicon carbide, calcium fluoride, boron nitride, barium sulfate, molybdenum disulfide, forsterite, and potassium carbonate whiskers. Two or more of these may be used in combination.
[0071] Among these, at least one selected from the group consisting of silica, titanium oxide, alumina and forsterite is particularly preferred from the viewpoint of low loss, and silica is most preferred.
[0072] It is particularly preferable that the spherical filler is composed of only spherical silica. As mentioned above, the purpose of blending the filler is to reduce the linear expansion coefficient, but if a filler with high anisotropy is blended, it becomes difficult to satisfy each of the above-mentioned dielectric properties. The spherical silica is preferable in that it has small anisotropy and frequency dependency of the relative dielectric constant.
[0073] The spherical silica particles refer to particles whose particle shape is close to a perfect sphere, and specifically, the sphericity is preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, and most preferably 0.95 or more. The sphericity is calculated by taking a photograph with an SEM and calculating the value from the area and perimeter of the observed particle as (sphericity) = {4π x (area) ÷ (perimeter) 2}. The closer to 1, the closer to a perfect sphere. Specifically, the average value measured for 100 particles using an image processing device (Spectris Corporation: FPIA-3000) is used.
[0074] The spherical silica particles used in the present disclosure preferably have a D90 / D10 of 2 or more (preferably 2.3 or more, 2.5 or more) and a D50 of 10 μm or less when the volume is integrated from the smallest particle size. Furthermore, it is preferable that the D90 / D50 is 1.5 or more (more preferably 1.6 or more). It is preferable that the D50 / D10 is 1.5 or more (more preferably 1.6 or more). Since the small particle size spherical silica particles can enter the gaps between the large particle size spherical silica particles, it is possible to achieve excellent filling properties and high fluidity. In particular, it is preferable that the particle size distribution has a high frequency on the small particle size side compared to a Gaussian curve. The particle size can be measured by a laser diffraction scattering type particle size distribution measuring device. It is also preferable that coarse particles having a particle size of a predetermined size or more are removed by a filter or the like.
[0075] The spherical silica particles preferably have a water absorption of 1.0% or less, more preferably 0.5% or less. The water absorption is based on the mass of the silica particles when dry. The water absorption is measured by leaving a sample in a dry state at 40°C and 80% RH for 1 hour, and measuring the water generated by heating at 200°C using a Karl Fischer water content meter, and then calculating the water absorption.
[0076] Alternatively, the spherical silica particles can be measured for each of the parameters by heating the dielectric at 600° C. for 30 minutes in an air atmosphere to burn off the fluororesin, and then extracting the spherical silica particles.
[0077] The silica particles used in the present disclosure may be surface-treated. By performing surface treatment in advance, the aggregation of the silica particles can be suppressed, and the silica particles can be well dispersed in the resin composition. In addition, it is also preferable that the dielectric loss tangent can be reduced.
[0078] The surface treatment is not particularly limited, and any known surface treatment can be used.Specific examples include treatment with a silane coupling agent such as epoxysilane, aminosilane, isocyanatesilane, vinylsilane, acrylicsilane, hydrophobic alkylsilane, phenylsilane, and fluorinated alkylsilane having a reactive functional group, plasma treatment, and fluorination treatment.
[0079] Examples of the silane coupling agent include epoxy silanes such as γ-glycidoxypropyltriethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, amino silanes such as aminopropyltriethoxysilane and N-phenylaminopropyltrimethoxysilane, isocyanate silanes such as 3-isocyanatepropyltrimethoxysilane, vinyl silanes such as vinyltrimethoxysilane, and acrylic silanes such as acryloxytrimethoxysilane.
[0080] The spherical silica particles may be commercially available silica particles that satisfy the above-mentioned properties. Examples of commercially available silica particles include Denka fused silica FB grade (manufactured by Denka Co., Ltd.), Denka fused silica SFP grade (manufactured by Denka Co., Ltd.), Excelica (manufactured by Tokuyama Corporation), high-purity synthetic spherical silica particles Admafine (manufactured by Admatechs Co., Ltd.), Admanano (manufactured by Admatechs Co., Ltd.), Admafuse (manufactured by Admatechs Co., Ltd.), etc.
[0081] More specifically, it is particularly preferable that the surface is treated with aminopropylsilane, aminosilane, vinylsilane, hydrophobic alkylsilane, phenylsilane, 3-mercaptopropylsilane, 3-acryloxypropylsilane, 3-methacryloxypropylsilane, p-styrylsilane, silylpropylsuccinic anhydride, 3-isocyanatopropylsilane, 2-(3,4-epoxycyclohexyl)ethylsilane, or the like. By carrying out surface treatment with these silane coupling agents, the polar functional groups present on the filler surface react, and the amount of the polar functional groups is reduced, resulting in excellent electrical properties.
[0082] (composition) The dielectric of the present disclosure contains the above-mentioned filler and fluororesin. If necessary, it may contain components other than the filler and fluororesin, or may consist of only the filler and fluororesin. The content of components other than the filler and fluororesin is preferably 10% by weight or less.
[0083] The dielectric of the present disclosure preferably has a filler content of 70% by weight or less based on the total amount of the composition. By including the filler in such a range, the linear expansion coefficient can be reduced, which is preferable in that the moldability is improved. The lower limit of the amount of the filler to be blended is not particularly limited, but from the viewpoint of being able to reduce the linear expansion coefficient, it is preferably 40% by weight. The upper limit is more preferably 68% by weight, and even more preferably 65% by weight, and the lower limit is more preferably 40% by weight, and even more preferably 45% by weight.
[0084] The dielectric of the present disclosure preferably has a linear expansion coefficient of 10 to 100 (ppm / °C). The above range is preferable in that the dielectric has low shrinkage and excellent dimensional stability. The upper limit is more preferably 90, and even more preferably 80. The lower limit is more preferably 12, and even more preferably 15. The linear expansion coefficient in this specification was determined by performing TMA measurement in a tensile mode using a TMA-7100 (manufactured by Hitachi High-Tech Science Corporation), using a sheet cut to a length of 20 mm, width of 5 mm, and thickness of 0.1 to 0.5 mm as a sample piece, setting the chuck distance to 10 mm, and applying a load of 49 mN at a heating rate of 2°C / min from -10 to 160°C, and calculating the linear expansion coefficient from the displacement of the sample.
[0085] (Method of manufacturing fluororesin sheet) When the fluororesin is polytetrafluoroethylene, the fluororesin sheet of the present disclosure can be obtained by mixing fluororesin particles and a filler to form a film. The manufacturing method is not limited, but can be performed by paste extrusion molding, powder rolling molding, etc. In the case of a melt-moldable fluororesin resin, the manufacturing method is not limited, but can be performed by injection molding, blow molding, inflation molding, vacuum / pressure molding, extrusion molding, etc., and the device used for melt kneading is not particularly limited, and a twin-screw extruder, single-screw extruder, multi-screw extruder, tandem extruder, etc. can be used.
[0086] As described above, it is preferable to use a fluororesin that cannot be melt molded as the fluororesin used in the fluororesin sheet of the present disclosure. When using such a fluororesin, when molding it into a sheet, it is preferable to mold it by fibrillating powdered PTFE as a raw material.
[0087] The powdered PTFE preferably has a primary particle size of 0.05 to 10 μm. The use of such PTFE has the advantage of excellent dispersibility. The primary particle size here is a value measured in accordance with ASTM D 4895.
[0088] The powdered PTFE preferably contains 50% by mass or more, more preferably 80% by mass or more, of polytetrafluoroethylene resin having a secondary particle diameter of 500 μm or more. By containing PTFE having a secondary particle diameter of 500 μm or more within this range, it is advantageous in that a composite sheet with high strength can be produced. By using PTFE with a secondary particle size of 500 μm or more, a composite sheet with lower resistance and excellent toughness can be obtained.
[0089] The lower limit of the secondary particle diameter is more preferably 300 μm, and even more preferably 350 μm. The upper limit of the secondary particle diameter is more preferably 700 μm or less, and even more preferably 600 μm or less. The secondary particle diameter can be determined, for example, by a sieving method.
[0090] The powdered PTFE mentioned above allows the production of fluororesin sheets with higher strength and excellent homogeneity. Therefore, the average primary particle size is preferably 50 nm or more. More preferably, it is 100 nm or more, even more preferably, it is 150 nm or more, and particularly preferably, it is 200 nm or more. The larger the average primary particle size of PTFE, the more suppressed the increase in paste extrusion pressure when the powder is used for paste extrusion molding, and the more excellent the moldability. The upper limit is not particularly limited, but may be 500 nm. From the viewpoint of productivity in the polymerization process, it is preferably 350 nm.
[0091] The above average primary particle diameter can be determined by preparing a calibration curve of the transmittance of 550 nm projected light per unit length of an aqueous dispersion of PTFE obtained by polymerization, the polymer concentration of which is adjusted to 0.22% by mass, and the average primary particle diameter determined by measuring the unidirectional diameter in a transmission electron microscope photograph, measuring the above transmittance for the aqueous dispersion to be measured, and then based on the calibration curve.
[0092] The PTFE used in the present disclosure may have a core-shell structure.The PTFE having a core-shell structure may include, for example, modified polytetrafluoroethylene, which contains a core of high molecular weight polytetrafluoroethylene and a shell of lower molecular weight polytetrafluoroethylene or modified polytetrafluoroethylene in a particle.As such modified polytetrafluoroethylene, for example, the polytetrafluoroethylene described in JP-A-2005-527652 may be included.
[0093] The specific methods for paste extrusion molding and powder rolling molding are not particularly limited, but the general methods are described below.
[0094] (Paste extrusion molding) The method for producing the sheet may include the steps of: mixing the PTFE powder obtained by using a hydrocarbon surfactant with an extrusion aid (1a), paste extrusion molding the mixture (1b), rolling the extrudate obtained by extrusion molding (1c), drying the rolled sheet (1d), and firing the dried sheet to obtain a molded product (1e). The paste extrusion molding may also be performed by adding conventional additives such as pigments and fillers to the PTFE powder.
[0095] The extrusion aid is not particularly limited, and generally known ones can be used, such as hydrocarbon oils.
[0096] (Powder rolling molding) The sheet can also be formed by powder rolling molding. Powder rolling molding is a method in which a resin powder is fibrillated by applying a shear force to the resin powder, and then molded into a sheet. The method may include a step of subsequently firing the powder to obtain a molded body. More specifically, A step (1) of applying a shear force to a raw material composition containing a fluororesin and a filler while mixing the raw material composition. A step (2) of forming the mixture obtained by the step (1) into a bulk form; and A step (3) of rolling the bulk mixture obtained in the step (2) into a sheet. The composition can be obtained by a manufacturing method having the following steps. When forming a sheet by such powder rolling molding, it is preferable to mix only the fluororesin particles and the inorganic filler and mold the mixture.
[0097] (Laminate) The dielectric material of the present disclosure can be used as a sheet for printed wiring boards by laminating it with other substrates.
[0098] A copper clad laminate can also be formed by adhering a copper foil to one or both sides of the dielectric material described above. As described above, the film containing the fluororesin of the present disclosure can be particularly suitably used in printed wiring board applications, and therefore can be suitably used as such a copper clad laminate.
[0099] The copper foil preferably has an Rz of 1.6 μm or less. That is, the fluororesin composition of the present disclosure has excellent adhesion to copper foil having a high smoothness of Rz of 1.6 μm or less. Furthermore, the copper foil only needs to have a thickness of 1.6 μm or less on at least the surface that is bonded to the above-mentioned fluororesin film, and there is no particular restriction on the Rz value of the other surface.
[0100] The thickness of the copper foil is not particularly limited, but is preferably in the range of 1 to 100 μm, more preferably in the range of 5 to 50 μm, and even more preferably in the range of 9 to 35 μm.
[0101] The copper foil is not particularly limited, and specific examples thereof include rolled copper foil and electrolytic copper foil.
[0102] The copper foil having Rz of 1.6 μm or less is not particularly limited, and commercially available products can be used. Examples of commercially available copper foil having Rz of 1.6 μm or less include electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil & Powder Co., Ltd.).
[0103] The copper foil may be surface-treated to increase the adhesive strength with the fluororesin film of the present disclosure.
[0104] The surface treatment is not particularly limited, but may be a silane coupling treatment, a plasma treatment, a corona treatment, a UV treatment, an electron beam treatment, etc., and the reactive functional group of the silane coupling agent is not particularly limited, but from the viewpoint of adhesion to the resin substrate, it is preferable to have at least one selected from an amino group, a (meth)acrylic group, a mercapto group, and an epoxy group at the end. In addition, the hydrolyzable group is not particularly limited, but may be an alkoxy group such as a methoxy group or an ethoxy group. The copper foil used in the present disclosure may have an anti-rust layer (such as an oxide film such as chromate), a heat-resistant layer, etc. formed thereon.
[0105] The surface-treated copper foil having a surface treatment layer of the above-mentioned silane compound on the copper foil surface can be produced by preparing a solution containing the silane compound and then surface treating the copper foil with this solution.
[0106] The copper foil may have a roughening treatment layer on the surface thereof from the viewpoint of improving adhesion to a resin substrate. In addition, if there is a risk that the roughening treatment will degrade the performance required in the present disclosure, the amount of roughening particles electrodeposited on the copper foil surface can be reduced as necessary, or the roughening treatment can be omitted.
[0107] Between the copper foil and the surface treatment layer, one or more layers selected from the group consisting of a heat-resistant treatment layer, a rust-proofing treatment layer, and a chromate treatment layer may be provided in order to improve various properties. These layers may be a single layer or multiple layers.
[0108] The copper-clad laminate may further include a layer other than the copper foil and the dielectric material. The layer other than the copper foil and the fluororesin film is preferably at least one selected from the group consisting of polyimide, modified polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether, modified polyphenylene ether, and polybutadiene.
[0109] The layers other than the copper foil and the dielectric are not particularly limited as long as they are made of the above-mentioned resins. In addition, the layers other than the copper foil and the fluororesin film preferably have a thickness in the range of 12.5 to 260 μm.
[0110] In the above copper-clad laminate, the copper layer may be formed on one or both sides of the roll film. Methods for forming the copper layer include a method for laminating (adhering) copper foil to the surface of the roll film, a vapor deposition method, a plating method, and the like. Methods for laminating copper foil include a method using heat pressing. The heat pressing temperature may be from the melting point of the dielectric film -150°C to the melting point of the dielectric film +40°C. The heat pressing time is, for example, 1 to 30 minutes. The heat pressing pressure may be 0.1 to 10 MPa.
[0111] The above-mentioned copper-clad laminate is not particularly limited in its application, and is used as a circuit board. A printed circuit board is a plate-shaped component for electrically connecting electronic components such as semiconductors and capacitor chips, while at the same time arranging and fixing them in a limited space. There is no particular limit to the configuration of the printed circuit board formed from this copper-clad laminate. The printed circuit board may be any of a rigid board, a flexible board, and a rigid-flexible board. The printed circuit board may be any of a single-sided board, a board, a double-sided board, and a multilayer board (such as a built-up board). In particular, it can be suitably used for flexible boards and rigid boards. In particular, it can be suitably used as a printed circuit board for high frequencies of 110 GHz or more.
[0112] The circuit board is not particularly limited, and can be produced by a general method using the above-mentioned copper-clad laminate.
[0113] The laminate for a circuit board is also a laminate having a copper foil layer, the above-mentioned fluororesin film, and a base layer. The base layer is not particularly limited, but preferably has a fabric layer made of glass fiber and a resin film layer.
[0114] The glass fiber fabric layer is a layer made of glass cloth, glass nonwoven fabric, or the like. The glass cloth may be commercially available, and is preferably treated with a silane coupling agent to enhance affinity with the fluororesin. The glass cloth may be made of E glass, C glass, A glass, S glass, D glass, NE glass, low dielectric constant glass, etc., and is preferably made of E glass, S glass, or NE glass because of its easy availability. The fiber may be woven in either plain or twill weave. The thickness of the glass cloth is usually 5 to 90 μm, and preferably 10 to 75 μm, but it is preferable to use a glass cloth thinner than the fluororesin film to be used.
[0115] The laminate may use a glass nonwoven fabric as a fabric layer made of glass fibers. The glass nonwoven fabric is a fabric in which short glass fibers are fixed with a small amount of a binder compound (resin or inorganic substance), or a fabric in which the shape is maintained by entangling short glass fibers without using a binder compound, and a commercially available product can be used. The diameter of the short glass fibers is preferably 0.5 to 30 μm, and the fiber length is preferably 5 to 30 mm. Specific examples of the binder compound include resins such as epoxy resins, acrylic resins, cellulose, polyvinyl alcohol, and fluororesins, and inorganic substances such as silica compounds. The amount of the binder compound used is usually 3 to 15 mass % based on the short glass fibers. Examples of the material of the short glass fibers include E glass, C glass, A glass, S glass, D glass, NE glass, and low dielectric constant glass. The thickness of the glass nonwoven fabric is usually 50 μm to 1000 μm, and preferably 100 to 900 μm. The thickness of the nonwoven glass fabric in this application is measured in accordance with JIS P8118:1998 using a digital gauge DG-925 manufactured by Ono Sokki Co., Ltd. (Weight: 110 grams, surface diameter: 10 mm) The glass nonwoven fabric may be treated with a silane coupling agent to enhance its affinity with fluororesin.
[0116] Most nonwoven glass fabrics have a very high porosity of 80% or more, so it is preferable to use a sheet that is thicker than a sheet made of fluororesin and compress it by pressure.
[0117] The glass fiber fabric layer may be a layer in which a glass cloth and a glass nonwoven fabric are laminated together, whereby the properties of the two fabrics are combined to obtain suitable properties. The glass fiber fabric layer may be in the form of a prepreg impregnated with a resin.
[0118] In the above laminate, the glass fiber fabric layer and the fluororesin film may be bonded at the interface, or the glass fiber fabric layer may be partially or entirely impregnated with the fluororesin film. Furthermore, a prepreg may be prepared by impregnating a fabric made of glass fibers with the fluororesin composition. The prepreg thus obtained may be further laminated with the fluororesin film of the present disclosure. In this case, the fluororesin composition used in preparing the prepreg is not particularly limited, and the fluororesin film of the present disclosure may also be used.
[0119] The resin film used as the substrate layer is preferably a heat-resistant resin film or a thermosetting resin film. Examples of the heat-resistant resin film include polyimide, modified polyimide, liquid crystal polymer, polyphenylene sulfide, etc. Examples of the thermosetting resin include epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether, modified polyphenylene ether, polybutadiene, etc. The heat-resistant resin film and the thermosetting resin film may contain reinforcing fibers. The reinforcing fibers are not particularly limited, but for example, glass cloth, particularly low dielectric type, is preferable. The heat-resistant resin film and the thermosetting resin film are not particularly limited in terms of dielectric properties, linear expansion coefficient, water absorption rate, and other properties, but for example, the dielectric constant at 20 GHz is preferably 3.8 or less, more preferably 3.4 or less, and even more preferably 3.0 or less. The dielectric loss tangent at 20 GHz is preferably 0.0030 or less, more preferably 0.0025 or less, and even more preferably 0.0020 or less. The linear expansion coefficient is preferably 100 ppm / °C or less, more preferably 70 ppm / °C or less, and even more preferably 40 ppm / °C or less. The water absorption rate is preferably 1.0% or less, more preferably 0.5% or less, and even more preferably 0.1% or less. EXAMPLES
[0120] The present disclosure will now be described in detail with reference to examples. In the following examples, unless otherwise specified, "parts" and "%" represent "parts by mass" and "% by mass", respectively.
[0121] Sheet manufacturing method 1 (paste extrusion molding) The fluororesin powder (PTFE) and spherical silica were weighed out in the prescribed amounts shown in Table 3 and mixed in a mixer in the presence of dry ice. The temperature during mixing was -10°C or lower. Oil (IP Solvent 2028) was added to the resulting mixed powder at 18 to 23 wt %, mixed, and aged for about 5 hours. The aged composition was preformed under a pressure of 3 MPa, and the preformed compact was extruded at 40°C and 50 mm / min to obtain an extrusion sample. The extrusion sample was rolled with two rolls (roll gap: set to 500-80 μm) to obtain a sample with a film thickness of 125 μm. The sample was dried at 200°C for 2 hours and calcined at 360°C for 15 minutes to obtain a sheet.
[0122] Sheet manufacturing method 2 (powder rolling molding) The fluororesin powder (PTFE) and silica were weighed out in the proportions shown in Table 3 and stirred twice for 30 seconds at room temperature with a Wonder Crusher at memory setting 6. The resulting powder was rolled with two rolls (roll gap: set to 100 μm) to obtain a sample with a film thickness of 130 μm, and then baked at 360°C for 15 minutes to obtain a sheet.
[0123] The spherical silica used in each example was SC6500-SQ (average particle size: 2.1 μm) manufactured by Admatechs Co., Ltd., which was used as a raw material and was subjected to the surface treatment shown in Table 2 in some examples. The spherical silica used in Example 9 was FE920D-SQ (average particle size: 5.8 μm) manufactured by Admatechs Co., Ltd., and the spherical silica used in Example 10 was 20GA-C2 (average particle size: 2.0 μm) manufactured by Admatechs Co., Ltd.
[0124] The fluororesin powder (PTFE) used has the following properties: Average particle size: 500μm Apparent density: 460g / L Standard specific gravity: 2.17 Measurement method complies with ASTM D 4895
[0125] [Table 2]
[0126] [Table 3]
[0127] (etching) The copper foil with a resin layer (RO3003G2, NF-30) was etched with an aqueous solution of ferric chloride, washed with running fresh water for 2 to 5 minutes, washed with distilled water, and dried in a thermostatic chamber at 80±3°C for approximately 60 minutes to recover the individual resin layer.
[0128] Comparative Example 1 A commercially available copper-clad laminate, RO3003G2 (manufactured by Rogers), was etched to obtain a resin layer.
[0129] Comparative Example 2 A commercially available copper-clad laminate, NF-30 (manufactured by Taconic), was etched to obtain a resin layer.
[0130] (Evaluation method) (Method of measuring dielectric constant and dielectric loss tangent) The dielectric constant (Dk) and dielectric loss tangent (Df) at each frequency were measured using a network analyzer (N5290A, Keysight Technologies) and Fabry-Perot resonators J band (220-330 GHz) and D band (110-170 GHz) (FP-J, FP-D, EM Lab) at a room temperature of 25°C and humidity of 50%. The results are shown in Table 4.
[0131] [Table 4]
[0132] From Table 4, the dielectrics of Examples 1 to 10 have small differences in relative dielectric constants at frequencies from 220 to 330 GHz, and when such dielectrics are made into copper-clad laminates, it is not necessary to change the wiring width of the copper wiring for each frequency. In addition, a dielectric with small anisotropy of the relative dielectric constant at 170 GHz can be obtained, making it possible to freely design the copper wiring in a shape other than a straight line. Furthermore, it is preferable that the dielectric loss tangent (Df) for each frequency of 220 GHz and 330 GHz is low. By using a material with a low dielectric loss tangent, the transmission loss in the range of 220 to 330 GHz is reduced, which is preferable. [Industrial Applicability]
[0133] The dielectric material of the present disclosure can be suitably used in high frequency printed circuit boards, particularly at frequencies of 110 GHz or higher.
Claims
1. The slope of the relative permittivity (Dk) with respect to frequencies from 220 GHz to 330 GHz, measured in the J-band of a Fabry-Perot resonator, is between 0.00001 and 0.0005. A dielectric material characterized by containing a fluororesin, wherein the standard specific gravity of the fluororesin is 2.05 to 2.
2.
2. The relative permittivity (Dk) of the Fabry-Perot resonator measured in the D-band at 170 GHz has a 90° anisotropy in the plane direction of 0.02 or less. A dielectric material characterized by containing a fluororesin, wherein the standard specific gravity of the fluororesin is 2.05 to 2.
2.
3. The dielectric loss tangent (Df) at 220 GHz measured in the J-band of the Fabry-Perot resonator is 0.00153 or less. A dielectric material characterized by containing a fluororesin, wherein the standard specific gravity of the fluororesin is 2.05 to 2.
2.
4. The dielectric loss tangent (Df) at 330 GHz measured in the J-band of the Fabry-Perot resonator is 0.00165 or less. A dielectric material characterized by containing a fluororesin, wherein the standard specific gravity of the fluororesin is 2.05 to 2.
2.
5. The dielectric is the dielectric according to any one of claims 1 to 4, comprising a fluororesin and a spherical filler.
6. The dielectric according to claim 5, wherein the filler is at least one selected from the group consisting of silica, titanium oxide, alumina, and forsterite.
7. The dielectric according to claim 5, wherein the filler is substantially spherical silica.
8. The dielectric according to claim 5, wherein the filler has an average particle size of 0.1 to 10 μm.
9. The dielectric according to any one of claims 1 to 4, wherein the fluororesin is fibrillated, and comprises only the fluororesin and filler, and does not contain any other components.
10. The dielectric according to any one of claims 1 to 4, wherein the fluororesin is a part or all of at least one polymer selected from the group consisting of polytetrafluoroethylene resin, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, and tetrafluoroethylene-hexafluoropropylene copolymer.
11. The dielectric according to any one of claims 1 to 4, obtained using fluororesin particles having a primary particle diameter of 0.05 to 10 μm as a raw material.
12. The dielectric according to claim 11, wherein the fluororesin particles have a volume-based cumulative 50% diameter of 0.05 to 40 μm.
13. A dielectric material according to any one of claims 1 to 4, which is used in printed circuit boards for the terahertz band, dielectric materials for the terahertz band, or multilayer circuit boards for the terahertz band.
14. A dielectric according to any one of claims 1 to 4, having a sheet shape.
15. A method for manufacturing a dielectric according to claim 14, characterized by mixing fluororesin particles and a filler to form a film.
16. The method for manufacturing a dielectric according to claim 14, characterized by having a step of mixing fluororesin particles and filler and forming a film without adding any other components.
17. A copper-clad laminate used in terahertz-band printed circuit boards, terahertz-band dielectric materials, or terahertz-band multilayer circuit boards, wherein copper foil and the dielectric material described in claim 14 are essential layers.
18. A circuit board characterized by having a copper-clad laminate as described in claim 17.